Solar UV radiation measurements in Marambio, Antarctica, during years 2017–2019 ... : قياسات الأشعة فوق البنفسجية الشمسية في مارامبيو، أنتاركتيكا، خلال السنوات 2017–2019 ... - Margit Aun; Kaisa Lakkala; Ricardo Sánchez; Eija Asmi; Fernando Martín Nollas; Outi Meinander; Larisa Sogacheva; Veerle De Bock; Antti Arola; Gerrit de Leeuw; V. Aaltonen; David Bolsée; et al. (OpenAlex, 2020)
Abstract. In March 2017, measurements of downward global irradiance of ultraviolet (UV) radiation were started with a multichannel GUV-2511 radiometer in Marambio, Antarctica (64.23∘ S; 56.62∘ W), by the Finnish Meteorological Institute (FMI) in collaboration with the Servicio Meteorológico Nacional (SMN). These measurements were analysed and the results were compared to previous measurements performed at the same site with the radiometer of the Antarctic NILU-UV network during 2000–2008 and to data from five stations across Antarctica. In 2017/2018 the monthly-average erythemal daily doses from October to January were lower than those averaged over 2000–2008 with differences from 2.3 % to 25.5 %. In 2017/2018 the average daily erythemal dose from September to March was 1.88 kJ m−2, while in 2018/2019 it was 23 % larger (2.37 kJ m−2). Also at several other stations in Antarctica the UV radiation levels in 2017/2018 were below average. The maximum UV indices (UVI) in Marambio were 6.2 and 9.5 in 2017/2018 and ... : الخلاصة. في مارس 2017، بدأت قياسات الإشعاع العالمي الهابط للأشعة فوق البنفسجية (UV) بمقياس إشعاع GUV -2511 متعدد القنوات في مارامبيو، أنتاركتيكا (64.23درجة فهرنهايت ؛ 56.62درجة فهرنهايت)، من قبل المعهد الفنلندي للأرصاد الجوية (FMI) بالتعاون مع Servicio Meteorológico Nacional (SMN). تم تحليل هذه القياسات ومقارنة النتائج مع القياسات السابقة التي أجريت في نفس الموقع مع مقياس الإشعاع لشبكة NILU - UV في أنتاركتيكا خلال الفترة 2000–2008 ومع البيانات من خمس محطات عبر أنتاركتيكا. في عام 2017/2018، كان متوسط الجرعات اليومية الشهرية من الحمامي من أكتوبر إلى يناير أقل من متوسطها خلال الفترة 2000–2008 مع اختلافات من 2.3 ٪ إلى 25.5 ٪. في عام 2017/2018، كان متوسط جرعة الحمامي اليومية من سبتمبر إلى مارس 1.88 كيلو جولمتر مكعب، بينما في عام 2018/2019 كان أكبر بنسبة 23 ٪ (2.37 كيلو جولمتر مكعب). أيضًا في العديد من المحطات الأخرى في القارة القطبية الجنوبية، كانت مستويات الأشعة فوق البنفسجية في 2017/2018 أقل من المتوسط. كان الحد الأقصى لمؤشرات الأشعة فوق البنفسجية (UVI) في مارامبيو 6.2 و 9.5 في 2017/2018 و 2018/2019، على ...